SOFTWARE FOR RESEARCH OF DYNAMICS OF PROCESSES - Veitsblit, О.Й.; Korotaev , М.С. (Journal of Information Technologies in Education (ITE), 2020)
Since Newton research of dynamics of processes consists in construction of corresponding mathematical model and its careful studying. However investigation of any more or less real system is impossible without a computer and information technology. Computer simulation derives from two steps: (i) modeling, i.e. finding a model description of a real system, and (ii) solving the resulting model equations using computational methods. In the natural sciences it is often not so difficult to find a suitable model. On the other hand, due to computer simulations economics has entered the stage of deep transformation of its bases. However in economics the resulting equations are easier to solve, but they are harder to find. Therefore, here it is expedient and convenient to use a computer at the stage of modeling itself, i.e. on the model search stage. The С# desktop application Model specially intends for support process of modeling itself using computer. It is advisable and convenient to use specialized software for numerical experiments, which allows obtaining the model in a subject language, without codes; immediately afterwards all the necessary research tools already tuned to this model; easily modify the model depending on the results of the experiments. It was developed and continuously improved simultaneously and in close relationship with the construction of the theory of the general market model according to the new dynamic paradigm of economics, computational experiments via Model played a major role in the construction of this theory. As a result of this real and hard testing the latest version of Model has now reached some complete form and is submitted in this paper. In particular use of this software in educational process is reasonable: to concentrate attention to very uneasy subject - the process of research